The digital landscape in Eastern India: Findings from the digital needs assessment surveys from Bihar and Odisha, India - Adeeth Cariappa, Ajjikuttira Girish; Khed, Vijayalaxmi; Singaraju, Niyati; Gartaula, Hom N. (International Food Policy Research Institute, 2024)
This report examines the digital landscape in the Eastern Indian states of Bihar and Odisha, focusing on disparities in digital access, literacy, and technology utilization. Using gender-disaggregated data from 1,034 households, the findings reveal significant gender, social, and regional inequities. Women, especially from marginalized communities, face reduced access to digital devices, limited operational skills, and low internet usage for agricultural needs. Key barriers include high device costs, limited digital literacy, and inadequate local-language content. Despite challenges, a strong demand for digital skills training emerges, particularly among women and younger populations. The current utilization of mobile internet primarily revolves around communication and entertainment, with minimal use for agriculture-related activities. The report underscores the necessity for tailored digital literacy programs, localized content, and affordable technology to bridge these divides. Addressing these gaps can enhance the adoption of digital tools, fostering inclusive growth and improved agricultural outcomes in the region.